Persistent DNA Contamination in Competitive RT-PCR Using cRNA Internal Standards: Identity, Quantity, and Control. (June 2002) - Matthews, Jennifer L.K.; Chung, May; Matyas, John Robert
Accurate quantification of mRNA by competitive RT-PCR demands that the quality of the cRNA internal standard be strictly controlled and that at least two criteria should be satisfied. First, genomic DNA should be removed from the total RNA being analyzed; second, template DNA should be removed from the cRNA internal standard following in vitro transcription. We observed that the routine use of RNase-free DNase I is insufficient for removing template DNA from cRNA samples and can degrade cRNA. Furthermore, reducing the template DNA before digestion, selectively extracting template DNA, and gel fractionation are all ineffective at completely eliminating template DNA contamination in cRNA standards. A strategy was developed ("inverted" competitive RT-PCR) to quantify template DNA contamination in cRNA standards. Regardless of treatment method, a small percentage of DNA contamination remained in the products of in vitro transcription. Without correction, the number of mRNA copies calculated from competitive RT-PCR is systematically overestimated. The number of template DNAs contaminating the cRNA samples was remarkably large, though as a percentage of the total cRNA, DNA contamination was small and could be easily corrected.